Análise de estabilidade transitória em geradores distribuídos: considerações sobre a proteção 78PS. - HERINGER, Wesley Rodrigues (Universidade Federal do Pará, 2025)
This dissertation aims to present the transient stability analysis in Distributed Generators, considering the performance of 78PS protection, against loss of synchronization. In this context, the studies developed in this work will be considered For two distinct real cases of two cogeneration plants with synchronous generators of different powers, being a sugar-alcohol plant, which will soon be connected to An extensive rural feeder of Equatorial Energia’s Paragominas 34.5 kV substation, being in the second case analyzed a fruit pulp industry that uses biomass Resulting from the processes as fuel for the steam boiler, which connects to the a turbine, to drive a generator. In turn, this system will be interconnected in a predominantly urban feeder, in a distribution substation of 13.8 kV at Castanhal in the interior of Pará. The analyses are carried out by means of complete simulation in the time domain through software Anatem© , considering two modes of voltage control of synchronous machines: 1) without voltage control; and 2) with voltage control. The studies provide the margins of transient stability of the machines and considerations on the protection against the loss of timing of synchronous generators. The results indicate that the use of the voltage control mode of the automatic voltage regulator and the coordination between the protection of the internal feeders of the industrial consumer and the protection of the plant are fundamental to ensure the maintenance of the timing of distributed generation.